Persuasive Communication, Fear of Missing Out (FOMO), and Impulse Buying in Live Shopping: A Literature Review - Adinda Astari; Azhar Malik; Muhammad Ibrahim (Institut Manajemen Wiyata Indonesia, 2026)
The development of live shopping has brought significant changes to business communication patterns and consumer behavior in the era of social commerce. Direct interaction between hosts and audiences through digital platforms such as TikTok and Shopee creates a form of persuasive communication capable of influencing emotions and consumer purchasing decisions rapidly. This study aims to analyze the relationship between persuasive communication, Fear of Missing Out (FOMO), and impulse buying behavior in digital live shopping activities. The research employs a qualitative approach using a literature study method, reviewing various national and international journals published between 2020 and 2025. Data were obtained from academic databases such as Google Scholar, ScienceDirect, Scopus, and ResearchGate. The results indicate that persuasive communication by live shopping hosts plays a critical role in capturing attention, fostering emotional engagement, and building consumer trust. Communication strategies employed include emotional appeal, urgency marketing, scarcity strategy, social proof, and real-time interaction with the audience. Moreover, live shopping features such as countdown timers, limited stock, flash sales, and notifications of other users’ purchase activities reinforce consumers’ sense of FOMO. This psychological condition, in turn, encourages impulse buying, leading to spontaneous purchases without prior planning. Applying the S-O-R (Stimulus–Organism–Response) model, these stimuli trigger FOMO as the organism and generate unplanned purchases as the response. Therefore, the success of live shopping depends not only on product quality but also on creating interactive, emotional, and socially engaging digital experiences.